SUSTAINABILITY THRU’ PUBLIC UTILITIES HOW DEWA DUBAI DIFFERENTIATES FROM OTHERS - L. A. Mohan; S. Sayel (Экономика: стратегия и практика, 2018)
The research paper analyses the emergent role of public utility organizations in fostering sustainability and green society and, researches recent innovations and initiatives of Dubai Electricity and Water Authority (DEWA). The research paper outlines how DEWA has expanded her role as public utility by focusing strongly on the importance and mission of sustainability and differentiated itself from others in the world by benchmarking the best in the world and in many cases, setting new international standards and best practices in sustainable societies and utilities ecospace. In recent years, DEWA has launched a slew of initiatives in sustainability, quality and excellence to launch the Emirate of Dubai into a green orbit. Our research product underlines the mission and vision of DEWA as it relates to the domain of sustainability, how it differentiates form others and measures the impact of two sustainability initiatives on the stakeholders.